(untitled) (European Journal of Health Research, 2020)
Prematurity is one of the main issue of perinatal health; taking into account its high incidence, the morbidity shown in the short and long term and the scarce scientific evidence that determines the influence that risk factors have on motor development in preterm infants, we propose to conduct a study that will analyse the influence that perinatal factors risk have on the gross motor development of this population. Method is based on: cross-sectional observational study on a sample of 261 preterm infants, evaluated from November 2014 to April 2018. The Alberta Infant Motor Scale (AIMS) was used to assess the level of gross motor development, the percentile in which is the premature one and the Perinatal Risk Inventory (PERI) to determine the score and the level of perinatal risk. Results are a significant and inverse relationship between perinatal risk and gross motor skills is found in both sexes (p = 0.000). So, the gross motor development of preterm infants is lower as the level of perinatal risk increases. Intracranial hemorrhage and gestational age are the perinatal risk factors that have shown the greatest influence on the gross motor development of preterm infants.